Parenting style trends before and during the COVID-19 pandemic: a bibliographic study - Nuraeni; Ayubi, Dian (BKM Public Health and Community Medicine, 2023)
Purpose: This bibliometric research seeks to find differences in parenting research trends before and during the COVID-19 pandemic, particularly in the distribution of publications by country, author, and publication source. In addition, we analyze the differences in collaboration networks and keywords. Methods: The data comes from the Scopus.com database with the keywords "parenting AND style", the distribution of publications in 2016-2018 represents the pre-pandemic period, and 2020-2022 represents the period when the COVID-19 pandemic occurred. Acquisition data is stored in comma-separated value (CSV) format and analyzed using the VOSviewer application. Results: An increase in publications was found during the COVID-19 pandemic. The United States (US) had the most publications before and during the pandemic, followed by strengthening cooperation with China. Before the COVID-19 pandemic, the Journal of Child and Family Studies dominated publications with three network clusters. Hughes S.O. is the most author and the Pinquart with the most quotes. Meanwhile, the International Journal of Environmental Research and Public Health dominated publications during the pandemic. Garcia O.F. is the author with the most publications and citations. Finally, parenting styles is a keyword that often appears before and during a pandemic. Conclusion: The distribution of parenting style publications before and during the pandemic fluctuated but cumulatively increased. Meanwhile, there has also been a shift based on sources and countries with cooperative networks. In addition, topics related to parenting styles during the COVID-19 pandemic intersect with crisis conditions due to the pandemic, and there has been an increase in mental health topics.